Current Trends in Nanoscale Interfacial Electrode Engineering for Sulfide‐Based All‐Solid‐State Li‐Ion Batteries. Issue 5 (27th March 2021) - Ali, Mukarram; Doh, Chil-Hoon; Lee, You-Jin; Kim, Byung-Gon; Park, Jun-Woo; Park, Junho; Park, Gumjae; Lee, Won-Jae; Lee, Sang-Min; Ha, Yoon-Cheol
Abstract : All‐solid‐state Li‐ion batteries (ASSLBs) have been a topic of interest in the recent two decades for use in energy storage technologies. Among various types of solid electrolytes, sulfide‐based solid electrolytes (SSEs) have been regarded as the most promising electrolytes for practical ASSLBs due to their high ionic conductivity (>1 mS cm −1 ) and the possibility of high energy density cells (>500 Wh kg −1 ) using a currently available high capacity oxide cathode and a Li‐metal anode, as well as their nonflammable nature. However, SSEs are known to suffer from: 1) low electrochemical stability window; 2) parasitic interfacial reactions at oxide cathodes; 3) electrochemomechanical degradation at the interface; and 4) dendritic growth at bare Li‐metal anodes. Herein, a comprehensive review of specific strategies for high energy density ASSLBs is provided, focusing on the nanoscale interfacial engineering on oxide‐based cathode materials and Li‐metal anodes. Recent progresses in in situ‐based complex interfacial coatings, deposition techniques for synthesizing complex core–shell structures at oxide‐based cathode active materials, and lithiophilic seeding followed by dendrite protective coatings at anodes are mainly summarized. Finally, the perspectives for the development of high energy density sulfide‐based ASSLBs are highlighted. Abstract : Sulfide solid electrolytes have been studied for decades as an alternative for flammable liquid electrolytes used in commercial Li‐ion batteries. Despite their excellent properties such as superionic conductivity, several interfacial challenges still hinder the practical adoption in all‐solid‐state batteries. This review summarizes and discusses nanoscale interfacial engineering methods to tackle those critical issues.